Peranan Kredit Usaha Rakyat Dalam Pemberdayaan Pelaku Usaha Di Karawang (Studi Kasus Bank Rakyat Indonesia Cabang Karawang) - Karimah, Rima Latiefah; Nopiana, Medi (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to describe the role of the Bank Rakyat Indonesia Banking Financial Institution in Empowering Micro, Small, and Medium Enterprises. This research uses a qualitative descriptive approach. The results obtained by the community are still reluctant to borrow capital through financial institutions due to complicated procedures, while showing that BRI through the People's Kredit Usaha Rakyat program (KUR) can help the progress of UMKM and UKMs, especially in Karawang Regency, through financing and empowerment with low-interest rates. . From the findings, BRI needs to take several approaches to the community, to create trust and change the negative stigma with the KUR program at Bank Rakyat Indonesia.